Evaluation of Electropolishing Characteristics of 316L Stainless Steel Tube in Contaminated Electrolyte - Woo-Chul Jung; Hyunseok Yang; Seon-Jin Choi; Man-Sik Kong (Archives of Metallurgy and Materials, 2024)
In the electropolishing process, the polishing quality of the metal surface varies according to the contamination of the electrolyte. In this study, the electrolyte was evaluated according to the usage time, and the effect of each factor on electropolishing was investigated. As the electrolyte is contaminated, the concentration of metal ions in the electrolyte increases and the ion conductivity decreases. In addition, the pH and specific gravity of the electrolyte increase due to the metal sludge formed as the metal ion concentration increases. When the electrolyte usage time was more than 5 days, many scratches remained on the surface of 316L stainless steel, and relatively high surface roughness was measured. The surface roughness improvement rate compared to the initial specimen was 30% for the unused electrolyte, 26% on the 3rd day, 19% on the 5th day, and 17.5% on the 13th day. Since the low current density due to electrolyte contamination causes a decrease in polishing efficiency, initial scratches on the metal surface still exist on the polished surface. Therefore, it is necessary to manage the electrolyte to maintain the quality of electropolishing.